Maternal perceptions of sibling adaptation in Korean families of children with Down syndrome. (11th March 2014) - Choi, H.; Van Riper, M.
Abstract Background It is estimated that more than 500 infants with Down syndrome (DS) are born each year in Korea. DS affects not only these individuals, but family members as well. Some siblings deal successfully with the challenges of living with a child with DS and adapt well while others struggle or fail to adapt. The aims of this descriptive study were to explore how Korean mothers of children with DS perceive the adaptation of their typically developing (TD) children aged 4 to 19 and how family variables contribute to sibling adaptation. Method This descriptive, cross‐sectional study was conducted with 105 Korean mothers. Results Most mothers indicated that their TD children were not experiencing psychological or behavioural problems; however, many described problems in the sibling relationship. It was found that family factors (i.e. condition management effort, condition management ability, child's daily life, parental mutuality, family hardiness and social support) were strong predictors of sibling psychological, behavioural and relational adaptation. Demographic characteristics of the child with DS, the mother and the family appeared to significantly influence sibling adaptation. Conclusions These findings highlight the importance of familial contexts in understanding sibling adaptation. Knowledge of family factors associated with better adaptation in Korean siblings of child with DS will facilitate the development of culturally appropriate interventions for these children and their families. In addition, an awareness of demographic characteristics associated with sibling adaptation will help health care professionals identify siblings who are at increased risk of experiencing difficulties in adapting.